Chemical and biological impacts of ocean acidification along the west coast of North America. (20th December 2016) - Feely, Richard A.; Alin, Simone R.; Carter, Brendan; Bednaršek, Nina; Hales, Burke; Chan, Francis; Hill, Tessa M.; Gaylord, Brian; Sanford, Eric; Byrne, Robert H.; Sabine, Christopher L.; Greeley, Dana; et al.
Abstract: The continental shelf region off the west coast of North America is seasonally exposed to water with a low aragonite saturation state by coastal upwelling of CO2 -rich waters. To date, the spatial and temporal distribution of anthropogenic CO2 (Canth ) within the CO2 -rich waters is largely unknown. Here we adapt the multiple linear regression approach to utilize the GO-SHIP Repeat Hydrography data from the northeast Pacific to establish an annually updated relationship between Canth and potential density. This relationship was then used with the NOAA Ocean Acidification Program West Coast Ocean Acidification (WCOA) cruise data sets from 2007, 2011, 2012, and 2013 to determine the spatial variations of Canth in the upwelled water. Our results show large spatial differences in Canth in surface waters along the coast, with the lowest values (37–55 μmol kg −1 ) in strong upwelling regions off southern Oregon and northern California and higher values (51–63 μmol kg −1 ) to the north and south of this region. Coastal dissolved inorganic carbon concentrations are also elevated due to a natural remineralized component (Cbio ), which represents carbon accumulated through net respiration in the seawater that has not yet degassed to the atmosphere. Average surface Canth is almost twice the surface remineralized component. In contrast, Canth is only about one third and one fifth of the remineralized component at 50 m and 100 m depth, respectively. Uptake of Canth has caused the aragonite saturation horizon to shoal by approximately 30–50 m since the preindustrial period so that undersaturated waters are well within the regions of the continental shelf that affect the shell dissolution of living pteropods. Our data show that the most severe biological impacts occur in the nearshore waters, where corrosive waters are closest to the surface. Since the pre-industrial times, pteropod shell dissolution has, on average, increased approximately 19–26% in both nearshore and offshore waters. Graphical abstract: Highlights: The coastal waters off the US west coast are seasonally exposed to waters with low aragonite saturation. Large spatial differences in Canth occur in surface waters along the coast. Average surface Canth is almost twice the surface remineralized component (Cbio ). Uptake of Canth has caused the aragonite saturation horizon to shoal by approximately 30–50 m. Pteropod shell dissolution has increased approximately 19–26% since the pre-industrial era.